The great kapok tree : a tale of the Amazon rain forest - Cherry, Lynne (San Diego : Harcourt Brace Jovanovich, 1990)
The many different animals that live in a great kapok tree in the Brazilian rainforest try to convince a man with an ax of the importance of not cutting down their home.
"Gulliver books."
A col. map inserted.
G4
Keywords: Conservation of natural resources -- Fiction; Rain forests -- Fiction; Ecology -- Fiction; Kapok -- Fiction; Jungle animals -- Fiction